Dynamic exercise changes in venous pressure and liver stiffness in Fontan patients: effects of Treprostinil. (28th August 2021) - Possner, Mathias; Chaudhry, Anisa; Dillman, Jonathan R.; Urbina, Elaine M.; Gao, Zhiqian; McCoy, Connie; Faust, Michelle; Rossiter, Harry B.; Powell, Adam W.; Mays, Wayne; Veldtman, Gruschen
Abstract: Background: Systemic venous hypertension and low cardiac output are believed to be important mediators of liver injury after the Fontan procedure. Pulmonary vasodilators have the potential to improve such haemodynamics. The aim of this study was to assess the acute effects of exercise on liver stiffness and venous pressures and to assess the impact of inhaled Treprostinil on this response. Methods: In this prospective, double-blind, placebo-controlled, crossover trial, 14 patients with a Fontan circulation were randomised to inhalation of placebo and Treprostinil. Incremental and constant work rate exercise tests were performed to assess the effect of Treprostinil on exercise tolerance. Venous pressures were measured throughout and liver stiffness at rest and immediately after peak exercise. Results: Mean age was 27.8 ± 7.9 years and 66% were females. Exercise acutely increased liver stiffness by 30% (mean shear wave speed: 2.38 ± 0.71 versus 2.89 ± 0.51 ms, p = 0.02). Peripheral venous pressures increased acutely during both incremental (12.1 ± 2.4 versus 22.6 ± 8.0 mmHg, p < 0.001) and constant work rate exercise (12.5 ± 2.5 versus 23.4 ± 5.2 mmHg, p < 0.001). Overall, Treprostinil failed to attenuate exercise-induced increases in liver stiffness. Compared with placebo, Treprostinil did not significantly impact venous pressure responses, VO2 peak, nor exercise endurance times. Conclusions: Peripheral venous pressure increased acutely during exercise by an average of 88% above baseline and was not altered by administration of inhaled Treprostinil. Liver stiffness measured immediately post-exercise increased acutely by an average of 30%, with no attenuation following Treprostinil inhalation.